School Resonance with an Environmental Perspective (An ecological-based preservation) - Maslikhah, Maslikhah; Mukniah, Mukniah (Language Circle: Journal of Language and Literature, 2023)
The focus of the research is to find the resonance of ecologically-based schools. This research focus can be broken down into a number of questions. 1. How is the development of environmental care and cultured policies; 2. The development of an environment-based curriculum; 3. The development of community-based environmental activities; 4. The development and management of supporting facilities for caring and environmentally cultured schools; 5. The school's quest for a higher award? The research method used is qualitative research. The subjects of time and research were school principals, chief executives of the Adiwiyata program, and teachers of environmental education. The research location is SMA N 2 Temanggung, Central Java. The research was carried out from July to November 2016. Semi-structured interviews and in-depth interviews were used to collect data with the sample's goal in mind.The data analysis techniques used are interpretation, deduction, induction, and in-depth analysis. Checking the validity of the data through the degree of trust, transferability, dependability, and certainty. The results of the study were: 1. the development of a caring and cultured environment policy covering the principal's policy in developing the vision of a caring and environmentally cultured school, developing environmental education learning through integrated learning with existing subjects; increasing the capacity of human resources in the field of environmental education; saving natural resources, creating a clean and healthy school environment; and allocating and using funds for activities related to environmental issues. 2. Development of an environment-based curriculum through the application of a monolithic curriculum 3. Development of community-based environmental activities in the form of participatory activities 4. Development and management of supporting facilities for caring and environmentally oriented schools by carrying out strategic efforts through developing supporting facilities and improving management quality, saving natural resources, improving the quality of healthy food services, and achieving independence from waste management systems. 5. The school's efforts to get a higher award by implementing creative, innovative, and sustainable strategies, and building an environmentally friendly culture and lifestyle for students, teachers, and employees.